Longevity of Amalgam Build-Up Restorations in Endodontically Treated Teeth - Hamid Kermanshah; Sholeh Ghabraei; Mohammad Javad Kharrazifard; Marzieh Monjazeb; Negin Farahmandpour (Islamic Dental Association of Iran, 2018)
Background and Aim: Restoration of endodontically treated teeth is one of the most important and challenging topics in restorative dentistry. Longevity of such restorations is an essential factor in treatment planning. Amalgam build-up is a conservative method for restoration of endodontically treated teeth. Therefore, this study aimed to assess the longevity of this type of restoration in endodontically treated molar teeth. Materials and Methods: In this retrospective study, 110 endodontically treated molar teeth of 98 patients that had received amalgam build-up restorations with at least one cusp coverage with 3-10 years of longevity were evaluated. The restorations included mesio-occluso-distal (MOD;40%), disto-occlusal (DO;23%), mesio-occlusal (MO;17%) and complex amalgam restorations (20%). Binary logistic regression and Kaplan-Meier tests were used for statistical analysis. Results: Of all restorations, cracks were observed in 22.7% of restorative materials and 10.9% of teeth. Secondary caries was found in 29% of the teeth. Based on binary lo-gistic regression, MOD restorations had significantly higher rate of marginal fracture and recurrent caries (P<0.05). Teeth with one or four built-up cusps were significantly more resistant to fracture compared to other groups. Patients, who regularly used dental floss had significantly lower rate of secondary caries and restoration fracture (P=0.032). Conclusion: The average longevity of amalgam build-up restorations was 8.45 years, which is comparable to minimum longevity of casting restorations. Thus, amalgam restorations seem to be an acceptable conservative method for restoration of endodontically treated teeth.